Water removal during automated peritoneal dialysis assessed by remote patient monitoring and modelling of peritoneal tissue hydration - Joanna Stachowska-Pietka (Nature Portfolio, 2021)
Abstract Water removal which is a key treatment goal of automated peritoneal dialysis (APD) can be assessed cycle-by-cycle using remote patient monitoring (RPM). We analysed ultrafiltration patterns during night APD following a dry day (APDDD; no daytime fluid exchange) or wet day (APDWD; daytime exchange). Ultrafiltration for each APD exchange were recorded for 16 days using RPM in 14 patients. The distributed model of fluid and solute transport was applied to simulate APD and to explore the impact of changes in peritoneal tissue hydration on ultrafiltration. We found lower ultrafiltration (mL, median [first quartile, third quartile]) during first and second vs. consecutive exchanges in APDDD (−61 [−148, 27], 170 [78, 228] vs. 213 [126, 275] mL; p < 0.001), but not in APDWD (81 [−8, 176], 81 [−4, 192] vs. 115 [4, 219] mL; NS). Simulations in a virtual patient showed that lower ultrafiltration (by 114 mL) was related to increased peritoneal tissue hydration caused by inflow of 187 mL of water during the first APDDD exchange. The observed phenomenon of lower ultrafiltration during initial exchanges of dialysis fluid in patients undergoing APDDD appears to be due to water inflow into the peritoneal tissue, re-establishing a state of increased hydration typical for peritoneal dialysis.